PEMIKIRAN MU’TAZILAH - Pakpahan, Elpianti Sahara (Lembaga Jurnal dan Seminar Universitas Pembangunan Panca Budi, 2017)
Literally the word Mu'tazilah comes from I'tazalah which means separating or separating oneself which means also away or distancing themselves. Technically the term Mu'tazilah refers to two classes, namely: Thefirst group emerged as a pure political responses, this group grew as political neutrals, especially in the sense of being soft in dealing with the opposition between Ali bin Abi Talib and his opponents, especially Mu'awiyah, Aisyah, Thalhah and Abdullah bin Zubeir. It was this group that was originally called the Mu'tazilites because they distanced themselves from the issue of khilafah dispute. This group is neutral without the stigma of theology. The second group emerged as a response to the theological problems that developed among the Kharijites and Murji'ahs due to the events of Tahkim. This group emerged because they differed with the Khawarij and Murji'ah groups about giving the pagan status to the big sinner. This discussion topic is about: The perpetrator of the great sin, faith and kufr, the deeds and deeds of man, the nature of God, the absolute will of God and the justice of God.